Characterization of Pectobacterium carotovorum and P. wasabiae and their potential control using antagonistic bacteria - Golkhandan, Elham (2014)
In August 2011, vegetable crops showing symptoms of maceration and water soaked lesions on their tuber, leaf, and fruit were collected from four major vegetable growing states in Malaysia including Pahang, Johor, Melaka and Selangor. The majority of the causal organisms isolated from infected tissues (52 strains) were identified as Pectobacterium spp. based on PCR amplification of the pectate lyase (pel) gene and amplification of the 16S-23S rRNA (ITS) with G1 and L1 primers. Physiological and biochemical assays divided Malaysian Pectobacterium species into two main groups: Pectobacterium wasabiae and Pectobacterium carotovorum subsp carotovorum. Partial sequence of PCR product from reaction of putative Pectobacterium spp. with 16S rRNA confirmed the results obtained from physiological and biochemical assays used for identification of the bacterium. Application of specific primers such as Eca1F/Eca2r, Br1f/L1r, EXPCCF/EXPCCR, and also ITS-PCR following by RFLP by restriction enzyme (RsaI) successfully differentiated Malaysian P. wasabiae and P. carotovorum subsp carotovorum isolates from other species and subspecies of Pectobacterium. Phylogenetic analysis of Malaysian isolates with housekeeping genes (mdh, gapA) grouped Malaysian P. carotovorum subsp carotovorum and P. wasabiae in the same cluster with P. carotovorum subsp carotovorum (Ecc380) and P. wasabiae (SCRI488) respectively. In this study, some bacterial strains from the vegetable farm soil showed strong antagonistic activity against Pectobacterium carotovorum and Pectobacterium wasabiae in vitro on bell peppers, Chinese cabbage, cucumber, and tomato, and their cell-free filtered supernatants showed excellent biocontrol effect in controlling the potato maceration at room temperature. According to analysis of partial nucleotide sequences of 16S rRNA the isolates were identified as Pseudomonas chlororaphis, Pseudomonas fluorescens, Burkholderia cepacia, Bacillus subtilis, and Serratia liquefaciens. No significant differences in prevention of weight reduction by Pectobacterium spp. were observed between potato slices treated with antagonists andtreated with SH. Antibacterial agents isolated from Malaysian soils seem to be promising disinfectants to protect vegetables from soft rotting bacteria, and allow vegetables´ consumers and industries to reduce the amount of chemicals such as SH.